A systematic review and meta-analysis of the efficacy and safety of western medicine routine treatment combined with Chinese herbal medicine in the treatment of COVID-19. Issue 32 (7th August 2020) - Wang, Xuemei; Xie, Ping; Sun, Guojuan; Deng, Zhumei; Zhao, Min; Bao, Shuting; Zhou, Yunxia
Abstract: Background: COVID-19 is a global public health emergency. At present, there is no highly effective medicine for the prevention and treatment of 2019-nCoV. Western medicine for COVID-19 is mainly based on symptomatic support therapy. Chinese herbal medicine has been used to prevent infectious diseases for thousands of years in China. Western medicine routine treatment combined with Chinese herbal medicine is an alternative clinical option but lacks evidence-based medical evidence. The systematic review protocol aims to formulate a research plan that can evaluate the efficacy and safety of western medicine routine treatment combined with Chinese herbal medicine for COVID-19. Methods: We will search the following eight databases: Cochrane Library, PubMed, Embase, Medline, CNKI, Wanfang, VIP, and CBM. The search time is up to the end of July 2020. Two authors will independently complete literature screening, data extraction, and risk of bias assessment. In case of disagreement, the third author will assist in the judgment. The primary outcome will be the clinical cure rate. The secondary outcome will be accounting symptoms, fever time, time of virus nucleic acid turning negative, check the condition by drawing blood, pneumonia absorption rate, patient hospitalization time, severe conversion rate and case fatality rate, adverse reactions, and adverse events. Revman 5.3 will be used for systematic reviews and meta-analysis. The report of the protocol will follow the PRISMA-P statement, and the report of the systematic review and meta-analysis will follow the PRISMA statement. Results: We will provide evidence-based medical evidence of the efficacy and safety of western medicine routine treatment combined with Chinese herbal medicine for COVID-19. The findings will be published in peer-reviewed journals. Registration details: CRD42020190106.